IMPLEMENTASI KEPEDULIAN PESERTA DIDIK TERHADAP SAMPAH PADA KEGIATAN PLP 1 DI SEKOLAH DASAR - Lia Nurhayati; Rilis Monaalisa Adam (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
This study aims to analyze students’ environmental awareness toward waste management in the context of the School Field Introduction Program (PLP 1) at SDN 1 Limboto. The study was motivated by the persistence of waste in several school areas and the limited consistency of students in maintaining cleanliness. This research employed a qualitative descriptive approach using observation, semi-structured interviews, and documentation. The data were analyzed through thematic analysis covering data reduction, categorization, interpretation, and verification. The findings indicate that students’ waste awareness remains at the basic-awareness level: students understand the importance of cleanliness but have not consistently transformed this knowledge into daily habits. School efforts such as waste-disposal campaigns, class-cleaning schedules, teacher supervision, and habituation programs have supported environmental care, yet their impact depends on continuity and collective involvement. The study concludes that strengthening waste awareness requires sustained habituation, teacher modeling, supervision, and integration into daily school culture. PLP 1 provides an important reflective context for identifying real educational challenges and designing practical environmental-care strategies in elementary schools.